Magnetoresistive-coupled transistor using the Weyl semimetal NbP - Lorenzo Rocchino; Federico Balduini; Heinz Schmid; Alan Molinari; Mathieu Luisier; Vicky Süß; Claudia Felser; Bernd Gotsmann; Cezar B. Zota (Nature Communications, 2024)
Abstract Semiconductor transistors operate by modulating the charge carrier concentration of a channel material through an electric field coupled by a capacitor. This mechanism is constrained by the fundamental transport physics and material properties of such devices—attenuation of the electric field, and limited mobility and charge carrier density in semiconductor channels. In this work, we demonstrate a new type of transistor that operates through a different mechanism. The channel material is a Weyl semimetal, NbP, whose resistivity is modulated via a magnetic field generated by an integrated superconductor. Due to the exceptionally large electron mobility of this material, which reaches over 1,000,000 cm2/Vs, and the strong magnetoresistive coupling, the transistor can generate significant transconductance amplification at nanowatt levels of power. This type of device can enable new low-power amplifiers, suitable for qubit readout operation in quantum computers.